OBTAINING HALAL FOOD FOR INTERNATIONAL MUSLIM STUDENTS IN MUSLIM-MINORITY COUNTRIES - Farrah Febriastuti (SUJANA: Education and Learning Review, 2023)
The experiences of international Muslim students studying abroad are characterized by a careful balancing act between their academic endeavors and the maintenance of their cultural and religious identities in a world turning increasingly interconnected. When it comes to the many parts of daily life, eating habits are one that stands out as being closely associated with religious commitment. The availability of halal food, which complies with Islamic dietary regulations, becomes an important concern for Muslim students studying abroad. This research aims to identify how international Muslim students obtaining halal food in Muslim-minority countries. The method applied in this research is narrative literature review. The research findings identified that several international Muslim students studying abroad still have to fight for their rights to be provided by halal meals options within their schools, while another universities in another continents had recognize the dietary needs of their Muslim students and strive to provide halal food options on campus.